Directions in Reshaping Accountability Mechanisms in Multilateral Development Banks and Other Organizations. Issue 2 (20th December 2013) - Nanwani, Suresh
Abstract This article focuses on directions in reshaping accountability mechanisms in multilateral development banks and other organizations. The term 'accountability mechanisms' refers to avenues for private individuals and groups to file claims against the institution for redress of their grievance on poorly designed and/or implemented projects. Since 1993, accountability mechanisms have, over the years, been revised, updated or replaced. This article highlights the salient developments in reshaping accountability mechanisms and concludes with the directions taken and their impact on other institutions and development financiers in adopting similar mechanisms.